Pemanfaatan Buah Stoberi sebagai Pewarna Alami pada Rias Karakter Efek Luka - Windy Putri Rahmadani; Siska Miga Dewi (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This research is motivated by the use of artificial dyes that can cause toxicity and carcinogenesis to the skin, so that research was conducted to create natural dyes that are renewable, easily degraded, and environmentally friendly, one of which is natural dyes from strawberries. This study aims to analyze the results of the application of strawberries as natural dyes in character makeup with torn wounds in terms of color, adhesion, similarity and texture. This type of research is a quantitative pre-experimental research method. The object of this research is strawberries. The data analysis technique is descriptive analysis seen from color, adhesion, similarity, and texture. The results of the study are in terms of color, strawberries can be used as natural blood dyes in character makeup with torn wound effects because they have a thick color, namely blackish red, as evidenced by an average score of 3 with a blackish red color category. In terms of adhesion, strawberries can be used as natural blood dyes in character makeup with torn wound effects because they have sufficient adhesion, as evidenced by an average score of 3.14 with a fairly adhesive category. In terms of similarity, strawberries can be used as a natural blood dye in character makeup with torn wound effects because they are considered quite similar to real blood, as evidenced by an average score of 3.14 with a fairly similar category. In terms of texture, strawberries in the results of character makeup with torn wound effects can be used as a natural blood dye in character makeup with torn wound effects, as evidenced by an average score of 3 with a category of less smooth. It is recommended that students develop further research on strawberries as a natural dye to be used as a blood effect in character makeup with torn wounds.